Avaliação dos efeitos cardiovasculares induzidos pelo liofilizado do vinho tinto Garziera do Vale do São Francisco em ratos - Dellacqua, Melissa Negro (2012)
The aim of the present study was to evaluate the cardiovascular effects of Garziera red wine (Shiraz grape, vintage 2005) (GASH) of the Vale do São Francisco (Pernambuco Brazil) by using in vitro and in vivo approaches. Measurements of polyphenols levels in GASH revealed high levels of total phenolics compounds, quercetin and cis- and trans-resveratrol. Acute toxicity tests showed that GASH presented toxic effects only at doses 10-fold higher than the doses used in the in vivo experiments. Oral treatment with GASH at dose of 100 mg/kg/day for 7 days in normotensive rats did not promote significant differences in MAP and HR group treated with GASH (mmHg= 119.0 ± 2.02) compared to the control group (mmHg= 120.20 ± 2.04). In nonanesthetized SHR rats treated orally with GASH for 21 days at dose of 100 mg/kg/day, GASH decreased the MAP in the group treated (mmHg= 122.7 ± 1.52) compared to the control group (mmHg= 156.0 ± 5.39) and there was no change in HR. Similar results occurred with SHR rats and L-NAME hypertensive rats treated with GASH at dose of 100 mg/kg/day for 7 days, but the treatment for 21 days provides a greater reduction in the MAP. In non-anesthetized SHR rats, i.v administration of GASH promoted a biphasic effect, initially characterized by hypotension (ΔMAP= -39.40 ± 11.62) and bradycardia (ΔHR= -96.06 ± 44.34) followed by hypertension (ΔMAP= 69.4 ± 15.82) and tachycardia (ΔHR = 74.4 ± 35.95). Similar results occurred with LNAME hypertensive rats and normotensive rats. When comparing the results, the decrease in MAP is greater, and the bradycardia is smaller, in the L-NAME model and SHR model compared to normotensive rats. For the evaluation of hypotension and bradycardia in vivo, we performed the previous administration of L-NAME and atropine in normotensive rats and the hypotensive effect was attenuated and the bradycardia was abolished. Subsequently, experiments in rings of superior mesenteric artery isolated from normotensive rats showed that GASH-induced relaxation (Emax= 87.5 ± 6.5%) was significantly attenuated after removal of functional endothelium (Emax= 28.4 ± 4.9%), suggesting the involvement of endothelial-derived relaxing factors. Similar results were obtained with the previous incubation with L-NAME (Emax= 23.4 ± 5.1%) and ODQ (Emax= 11.8 ± 2.7%), suggesting the involvement of the NOS/NO/GMPc pathway in the relaxation. In rings of superior mesenteric artery isolated from normotensive rat, the previous incubation with indomethacin (Emax= 97 ± 4.1%) and atropine (Emax= 81 ± 3.9%) did not modify the relaxation induced by GASH, suggesting that arachidonic acid metabolites and M3 muscarinic receptor activation are not involved in this response. In endothelial cell line from rabbit aorta, GASH increased NO production (Δ= 82 ± 7.9%), which was reduced in the presence of L-NAME (Δ= 30.2 ± 12.1%), confirming the functional results. GASH promote the phosphorylation of eNOs and Akt in primary culture of endothelial cells from pig coronary by Western blot. Previous incubation with N-acetylcysteine in rings of superior mesenteric artery isolated from normotensive rats modified the relaxation induced by GASH (Emax= 32.5 ± 6.7%), suggesting the involvement of reactive oxygen species in the relaxation. GASH was able to increase levels of superoxide production in RAEC cell culture (Δ= 57 ± 4%). Using different methodological approaches in vivo and in vitro, this study suggests that GASH induces a antihypertensive effect in vivo in different models of hypertension, as well as an endothelium-dependent relaxing effect, probably secondary to an increase in the concentration of NO through the activation of the PI3k/Akt via, and suggest that these effects may be associated with the content of phenolic compounds found in GASH.